Application of confocal 3D-MXRF technology to the 3D elemental analysis and surface topography imaging of samples. Issue 1 (February 2020) - Xiang, Z J; Meng, Z Y; Liu, Z G; Pan, K; Zhao, W G; Zhou, P; Li, Y
Abstract: X-ray fluorescence analysis technology (XRF) is widely used in many fields. In this experiment, a three-dimensional confocal microbeam X-ray fluorescence analysis (3D-MXRF) spectrometer built by the laboratory is used to perform deep scanning on single element sample, surface coated sample, and ceramic sample, etc., the new spectrometer has deeper probing depth and better ability to resolve adjacent elements in the sample. The distribution of three-dimensional elements of samples is analyzed and explained. And the surface topography imaging of two samples is performed, and the newly constructed confocal 3D-MXRF was found to have a higher microscopic resolution, which plays a potential role in the popularization of surface inspection and 3D element analysis of industrial products.